2019
DOI: 10.21659/rupkatha.v11n2.16
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Classification of Dysphemisms in Artistic Discourse

Abstract: Due to the wide-spread use of dysphemisms in contemporary speech, the topic of dysphemia has become extremely important. At the same time, research on this issue is clearly not sufficient to cover this phenomenon in full. This study pursued the following goal: to analyze the morphological features of dysphemisms within the framework of artistic discourse. The concept of dysphemism was described, and a classification of dysphemisms in contemporary linguistics was provided. Dysphemisms represented by different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Andersson grouped swearing motifs into psychological, social, and linguistic motives (Karjalainen, 2002, p. 24). Prokhorova et al (2019) reported that nouns and adjectives are the most widely used in pronouncing harsh words or swear words.…”
Section: Introductionmentioning
confidence: 99%
“…Andersson grouped swearing motifs into psychological, social, and linguistic motives (Karjalainen, 2002, p. 24). Prokhorova et al (2019) reported that nouns and adjectives are the most widely used in pronouncing harsh words or swear words.…”
Section: Introductionmentioning
confidence: 99%